IoT Application in Cashier Systems to Help People with Disabilities (Deaf) - Muhammad Agung Nugroho, (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
The rapid development of the Internet of Things (IoT) has brought significant impact across various aspects of human life, including information systems and public services. One of its important applications lies in supporting inclusivity for people with disabilities. This research focuses on the implementation of IoT in a cashier system specifically designed to assist individuals with hearing impairments in conducting payment transactions more easily, independently, and equally. In conventional cashier systems, most transaction information is delivered through audio signals, which creates a barrier for hearing-impaired users in fully understanding the payment process. To address this issue, this study develops and implements a prototype of an IoT-based cashier system that utilizes visual notifications and digital indicators as the main medium for delivering transaction information.The results of testing indicate that the IoT-based cashier system functions effectively in delivering transaction information, reducing communication errors, and improving the independence of hearing-impaired users during the payment process. Therefore, this research contributes not only to the development of modern cashier systems but also to the advancement of inclusive and accessible technology that supports equal opportunities for all members of society.